Anoxia treatment for selectively controlling spider mites Tetranychus urticae and Panonychus citri with little impact on the predatory mite Neoseiulus californicus. Issue 4 (18th May 2016) - Wang, C.-H.; Suzuki, T.; Ohyama, K.; Ullah, M. S.; Gotoh, T.
ABSTRACT: Anoxia treatment with a deoxidant consisting of iron, calcium chloride and silicon dioxide was evaluated at different temperatures for pest spider mites ( Tetranychus urticae and Panonychus citri ) and their natural enemy, the predatory mite Neoseiulus californicus . No spider mite eggs survived when exposed to anoxia for 18 h at 20°C or for 12 h at 25°C, whereas the survival of N. californicus eggs under these conditions was 53% and 72%, respectively. No adult female spider mites survived when exposed to anoxia for 15 h at 20°C or for 8 h at 25°C, whereas >95% of adult N. californicus females survived under these conditions. These results indicate that anoxia has potential as a selective method for controlling pest mites, such as T. urticae and P. citri, but has little impact on their natural enemy, N. californicus .